A Lightweight Zero-Trust Architecture Implementation for Enhancing Cybersecurity in Small and Medium-Sized Enterprises - Dinh, Truong Duy; Le, Tran Duc; Nguyen, Thi Thu Ha; Do, Hoang Giang (Journal of Telecommunications and the Digital Economy, 2025)
Confronted by resource limitations and sophisticated cyber threats, Small and Medium Enterprises (SMEs) require tailored cybersecurity solutions. This research introduces and validates a Lightweight Zero-Trust Architecture (LZTA) specifically designed for SMEs. The proposed LZTA effectively integrates contextual access verification, multi-factor authentication, and role-based access control to ensure robust security without imposing excessive costs. Crucially, rigorous benchmarking demonstrated that the LZTA manages high-concurrency loads while significantly outperforming conventional and open-source Zero-Trust baselines in both response time and throughput. This work delivers a practical and high-performance blueprint for SMEs to adopt Zero-Trust principles, effectively balancing robust security with the operational constraints of smaller organisations.